Interactive Approaches in Arabic Language Teaching: Efforts to Improve Communication Skills - Syamfa Agny Anggara (JIPI (Jurnal Ilmiah Pendidikan Islam), 2025)
Interactive approaches have become one of the effective strategies in teaching Arabic, especially to improve students' communication skills. This study uses the literature review method to analyze the application of interactive strategies in Arabic language learning and its impact on students' speaking and listening skills. Data sources were obtained from scientific journal articles, books, and official education documents published in the last five years (2020–2025). The analysis is carried out qualitatively through data reduction, grouping of findings, and synthesis of information to identify best practices and implementation challenges. The results of the study showed that an interactive approach that combines collaboration, active participation, and the use of technology has been shown to improve communication skills, learning motivation, and student engagement. The main obstacles in the implementation of this strategy include limited resources, lack of teacher training, and resistance to new methods. This study provides insights for educators and policymakers in designing more effective and innovative Arabic language learning strategies.